ANALISIS EFEKTIVITAS VIDEO PEMBELAJARAN DALAM MEMBANGUN KARAKTER DISIPLIN DAN TANGGUNG JAWAB SISWA SD PADA MATA PELAJARAN PPKn - Ananda Pingka Afrija; Kurnia Marifatul Latifah; Ma'rifatul Luthfatun Nida; Arita Marini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
Learning videos are audio-visual media that are commonly used in teaching and learning activities in the 21st century. The purpose of this study was to find out how effective learning videos are applied in elementary schools to build students' character of discipline and responsibility. The methodology used is a qualitative method with a literature study approach. The form of the activity carried out was conducting library research through data collection using the listening technique, participatory observation taken from Google Schoolar with the keywords ``effectiveness of learning videos", "character of elementary school students' responsibility", and "discipline character of elementary students", and data analysis. The results obtained are that learning videos are effectively used in building a character of responsibility and discipline for elementary school students. Keywords: learning video, discipline character, responsibility character